Beyond Culture and Language: Access to Diabetes Preventive Health Services among Somali Women in Norway. (22nd July 2015) - Gele, Abdi A.; Torheim, Liv Elin; Pettersen, Kjell Sverre; Kumar, Bernadette
Abstract : Despite the high prevalence of type 2 diabetes in some immigrant and refugee communities in Norway, there is very little information available on their utilization of diabetes prevention interventions, particularly for women from Somali immigrant communities. A qualitative study of 30 Somali immigrant women aged 25 years and over was carried out in the Oslo area. Unstructured interviews were used to explore women's knowledge of diabetes, their access to preventive health facilities, and factors impeding their reception of preventive health programs targeted for the prevention of type 2 diabetes. The study participants were found to have a good knowledge of diabetes. They knew that a sedentary lifestyle and unhealthy diet are among the risk factors for diabetes. Regardless of their knowledge, participants reported a sedentary lifestyle accompanied with the consumption of an unhealthy diet. This was attributed to a lack of access to tailored physical activity services and poor access to health information. Considering gender-exclusive training facilities for Somali immigrant women and others with similar needs, in addition to access to tailored health information on diet, may encourage Somali women to adopt a healthy lifestyle, and it will definitely contribute to a national strategy for the prevention of diabetes.